Brucellosis in Endangered Hector's Dolphins (Cephalorhynchus hectori). (September 2017) - Buckle, Kelly; Roe, Wendi D.; Howe, Laryssa; Michael, Sarah; Duignan, Padraig J.; Burrows, E.; Ha, Hye Jeong; Humphrey, Sharon; McDonald, Wendy L.
Brucella spp infections of marine mammals are often asymptomatic but have been associated with reproductive losses and deaths. Zoonotic infections originating from marine isolates have also been described. Hector's dolphins (Cephalorhynchus hectori) are an endangered species with a declining population, and the role of infectious disease in population dynamics is not fully understood. In this study, 27 Hector's dolphins found dead around the New Zealand coastline between November 2006 and October 2010 were evaluated for lesions previously associated with cetacean brucellosis. Tissues were examined using histological, immunohistochemical, and molecular (polymerase chain reaction [PCR]) techniques. Seven of 27 dolphins (26%) had at least 1 tissue that was positive on PCR for Brucella spp. Lesions consistent with brucellosis were present in 10 of 27 (37%) dolphins, but in 8 of these dolphins Brucella infection could not be demonstrated in lesional tissues. Two dolphins (7%) were diagnosed with active brucellosis: 1 female with placentitis and metritis, and 1 stillborn male fetus. Brucella identified in these 2 dolphins had genetic similarity (99%) to Brucella pinnipedialis . The omp2a gene amplicon from the uterus of the female had 100% homology with ST27 genotype isolates from a human in New Zealand and a bottlenose dolphin of Pacific origin. The remaining 5 PCR-positive dolphins were assessed as having asymptomatic or latent infection. While most Brucella infections identified in this study appeared to be subclinical, the finding of 2 dolphins with reproductive disease due to Brucella infection suggests that this disease has the potential to affect reproductive success in this species.